A WAREHOUSE DESIGN WITH CONTAINERS FOR HUMANITARIAN LOGISTICS: A REAL-LIFE IMPLEMENTATION FROM TURKEY - Şahin-Arslan, Ayşenur; ERTEM, Mustafa Alp (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
The purpose of this study is to investigate how and at what cost freight containers could be used as an inventory holding mechanism for humanitarian logistics. The layout and cost comparison of two alternatives are performed—stocking in a warehouse and material storage in containers. An optimum layout for storage in containers is proposed. Leasing and purchasing option costs of these alternatives are compared using present worth analysis. The results revealed that the leasing option is not cost effective for both alternatives. Warehouse construction results in the least setup cost, but requires more area than a container stockpiling area. However, it incurs more operating costs, including lighting, ventilation, and maintenance as well as handling of the pallets. This study contributes to the research on warehouse design for humanitarian logistics with the novel idea of using containers as storage units. A real-life implementation of the concept of humanitarian material storage in containers is presented for Turkey.